2012
DOI: 10.1186/1749-8090-7-101
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pulmonary functional recovery after Nuss and Ravitch procedures for pectus excavatum repair: a meta-analysis

Abstract: BackgroundPectus excavatum (PE) is a common chest wall malformation, with surgery being the only method known to correct the defect. Although the Nuss and Ravitch procedures are commonly used, there is no consensus as to whether surgical repair improves pulmonary function. We therefore investigated whether pulmonary function recovers after surgical repair, and if recovery is dependent on the type of procedure or time after surgery.MethodsLiterature searches were performed using PubMed, EMBASE, Health Periodica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 40 publications
0
12
0
1
Order By: Relevance
“…Long-term results, however, are superior in grown-up patients, particularly for those who have completed their growth at the time of bar removal. Since regression or improvement of PE is not related to cartilage and ligament fixation, the ideal phase for optimal PE correction should be around adolescence, when the costal cartilages are still plastic and flexible 23 . In addition to this, since it is not negligible to share the indication for surgery among both parents and patient, at our Institution the procedure is carried out mainly in adolescents which are able to demonstrate a complete awareness of such surgical procedure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term results, however, are superior in grown-up patients, particularly for those who have completed their growth at the time of bar removal. Since regression or improvement of PE is not related to cartilage and ligament fixation, the ideal phase for optimal PE correction should be around adolescence, when the costal cartilages are still plastic and flexible 23 . In addition to this, since it is not negligible to share the indication for surgery among both parents and patient, at our Institution the procedure is carried out mainly in adolescents which are able to demonstrate a complete awareness of such surgical procedure.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 The post-operative cardiovascular and respiratory improvements are particularly applicable to patients with severe deformities, because surgery may increase significantly chest volume, making space available for lung expansion 29 . A recent meta-analysis including a total of 2476 PE patients operated with either techniques, showed that although both procedures for the correction of PE displayed the same improvements in pulmonary function within 1 year after the procedure, Nuss technique showed an additional enhancement in pulmonary function after bar removal 23 . In any case, there is still a need for further large-scale prospective trials and meta-analyses to better assess the extent of the beneficial effects of PE correction on pulmonary function.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative pulmonary function shows a long-term improvement after surgical correction of pectus excavatum [ 14 ]. However, the recently developed Nuss procedure, which relies on internal bracing for 2 to 4 years to reform the chest wall, has shown conflicting results with regard to pulmonary function in growing adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis that assessed pulmonary function recovery reported that the Nuss procedure was correlated with greater improvements in pulmonary function after bar removal, depending on the time after the operation [ 14 ]. In a long-term follow-up study, Sigalet et al reported a significant increase in FEV 1 and TLC after bar removal; however, they concluded that the pectus bar did not improve pulmonary dynamics shortly after the operation [ 6 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…As with FVC, VC initially favored the Ravitch procedure in the immediate postoperative period, however both increased significantly to favor the Nuss procedure at 3 years post surgery. TLC though was unchanged at 1 year was reported to be improved at 3 years with the Nuss procedure [17]. There is improvement in perceived exercise tolerance postoperatively, although PFTs may worsen, likely due to the combined cardiac and pulmonary changes.…”
Section: Cardiac and Pulmonary Function In Pectus Deformitiesmentioning
confidence: 91%